The Effectiveness of Molasses from a Mixture of Sugar Cane Juice and Brown Sugar - Dwi Rizaldi Hatmoko; Agustin Patmaningrum; Moh. Rifqi Fauzi (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the effectiveness of molasses produced from a mixture of sugarcane juice and brown sugar in terms of chemical composition, antioxidant activity, and its potential as a fermentation substrate for ethanol and lactic acid. The study used a literature review approach by reviewing relevant scientific articles, proceedings, and academic books from the last five to ten years. These sources were selected based on the clarity of the method, the relationship to molasses characteristics, and its use in functional foods and the bioindustry. The results of the study indicate that sugarcane molasses is rich in phenolics, flavonoids, and melanoidins with high antioxidant capacity, while brown sugar also has strong antioxidant activity and contributes minerals and Maillard compounds that play a role in redox activity. Sugarcane molasses has been proven effective as a fermentation substrate for the production of ethanol and lactic acid with competitive process performance and relatively low carbon source costs. Theoretically, molasses from a mixture of sugarcane juice and brown sugar has the potential to produce a sweet matrix with a high density of bioactive compounds and favorable fermentative characteristics. However, specific experimental data on the mixed molasses is still limited, so further research is needed to verify its chemical profile, actual antioxidant activity, safety, and fermentation performance.